The joy of syntax : a simple guide to all the grammar you know you should know - Casagrande, June (Ten Speed Press, 2018)
Includes index.; "When it comes to grammar, it seems like everyone--even die-hard word nerds--feels they "missed something" in school. The Joy of Syntax provides a fresh foundation served up by June Casagrande, a language columnist with an impressive record of making this otherwise inaccessible subject a true joy. With simple explanations for everything from basic parts of speech and sentence structure to usage and grammar pitfalls, this guide provides everything you need to approach grammar with confidence"